Asymmetries in the Euro area banking profitability - Veríssimo, P. (2021)
This paper shows how bank-specific, industry-specific, and macroeconomic determinants affect the profitability of 3046 banks across 19 Euro area countries, from 2006 to 2015. To assess the existence of potentially relevant asymmetries, we split our sample of Euro area banks into peripheral and core countries’ banks. Our results reveal that, compared to banks from core countries, the marginal effect of the loan loss provisions burden on profitability is, on average, at least 3 times larger in peripheral banks where a 1 p.p. increase in loan loss provisions reduces return on average assets by 0.6 p.p. Moreover, the impact of loan loss provisions on profitability levels during the 2008–2013 financial crisis period is found to be significantly more severe in peripheral banks. Our results likewise suggest that the improvement of efficiency levels and a more selective asset growth have stronger effects on the returns of peripheral banks. In contrast, the effect of customer deposits suggests that core countries’ banks make better use of this source of funding.